Challenges and Opportunities for Foreign Language Teachers in the Era of Artificial Intelligence - Yang, Aijun (Ilmu Inovasi Nusantara, 2024)
The emergence of large-scale language models such as ChatGPT has presented unprecedented challenges and opportunities in foreign language education. On one hand, artificial intelligence poses a disruptive crisis; on the other hand, it offers new educational insights, methodologies, and resources. Faced with these challenges and opportunities, university foreign language teachers must seize the opportunity to integrate intelligent technology into their teaching practices to enhance their teaching abilities and the quality of talent development. This study aims to investigate approaches for integrating artificial intelligence into foreign language teaching at the university level to improve teaching effectiveness and talent development outcomes. Through literature analysis and related research, the study identifies best practices and strategies for utilizing artificial intelligence in university foreign language education. The findings suggest that integrating artificial intelligence into foreign language teaching at the university level can significantly enhance teaching effectiveness and talent development. Thus, it is recommended that university foreign language teachers actively explore and implement artificial intelligence technology to enhance the quality of foreign language education and student talent development